SYN1lIESISOF 3-HYDROxy-3' ,4'-MElHYLENEDIOXy- 6" ,6" -DIMETHYLPYRANO (2",3":7 ,8) FLAVONE: Short Communication (Biological Sciences - PJSIR, 2001)
recorded on LKB 4053, England spectrophotometerUltrospeck in methanol (Arnax in nm). TLC performed usingsilica gel 60G. Mass spectra were recorded on VG 7070Eanalytical mass spectrometer. Elemental analyses were alsoobtained for all the compounds.